In Silico Study of Imidazole-Morpholine-1,2,4-Oxadiazole Derivatives as Candidate Breast Cancer Drugs via Molecular Docking Targeting ER-α, ADMET Analysis and Drug-Likeness Assessment - Herman, Mega Silpika Herman; Azra, Fajriah (Chemistry Department, Universitas Islam Indonesia, 2026)
Breast cancer is one of the leading causes of death among women worldwide. One of the causes of breast cancer is the overexpression of estrogen receptor alpha (Erα). Imidazole-morpholine-1,2,4-oxadiazole derivatives have been reported to exhibit cytotoxic activity against MCF-7 cells; however, their interaction with Erα has not yet been studied. This study aims to evaluate the potential of an imidazole-morpholine-1,2,4-oxadiazole derivative as a candidate anti-breast cancer drug using an in silico approach targeting Erα through molecular docking, as well as to predict the pharmacokinetic properties and toxicity of the compound using ADMET analysis. Molecular docking was performed using MOE 2019.0102 software with the Erα receptor (PDB: 3ERT), while ADMET predictions were conducted using pkCSM and swissADME software. The molecular docking results showed that the tested compounds exhibited good binding affinity for the target Erα receptor, specifically compound 7f, with a binding energy of -7.43 kcal/mol and an RMSD of 1.8 Å. Although compound 7f has a higher binding energy than tamoxifen, it still exhibits stable interactions at the active site of the ERα receptor, specifically with Leu346 and Glu353. Furthermore, the ADMET results indicate that compound 7f meets the criteria for drug candidacy based on Lipinski’s rules and ADMET predictions. However, it has drawbacks such as low permeability in Caco-2 cells, as well as being a P-gp substrate and exhibiting positive Ames toxicity and hepatotoxicity. Therefore, further experimental optimization and validation through in vitro or in vivo studies are necessary to improve the drug’s distribution and safety before proceeding with further development.